CONSTRAINTS TO NATIONAL UNITY AS PERCEIVED BY SELECTED ADULTS IN ILORIN METROPOLIS: IMPLICATIONS - FOR COUNSELLING - Esere, Ogechi Mary (Sokoto Educational Review, 2020)
This study investigated constraints to national unity as perceived by selected adults in Ilorin Metropolis. A total of 500 (mean age = 43.05; age range = 35 and 68 years; males = 294; females = 206) respondents participated in the study. The participants responded to the Constraints to National Unity Questionnaire (CNU). The data collected were analyzed using percentages, mean scores, standard deviation, t-test and Analysis of Variance (ANOVA) statistics. The results of the study revealed that religious bigotry, ethnicity and land encroachments constituted the major constraints to national unity. The results of this study have several implications for counselling in Nigeria. Through public awareness programmes, counsellors should address issues bordering on ethnic cooperation, and religious tolerance.